Dreaming about pain: dreams series of a chronic pain patient - Markert, Bettina; Schredl, Michael (Dreaming, 2025)
The occurrence of physical pain in the dreams of healthy individuals is relatively rare, while patient populations report pain more frequently in their dreams. This study conducted dream content analysis on a long dream series (N = 4,254) from a patient diagnosed with a chronic pain-inducing illness at a young age. We found that 9.76% of the dream reports referenced pain, experienced by the dreamer, other characters, or as a thematic element. The dreamer frequently reported pain in her whole body, limbs, and joints, suggesting a correspondence with her waking-life experiences with pain. The emotional tone of the pain dreams was predominantly negative, though occasional positive emotions reflecting relief from pain were observed. These findings highlight the multifaceted ways of integrating pain into dream content and suggest continuity between waking-life pain and pain dreams. Future research should explore the exact relationship between waking-life pain intensity and pain dream frequency in chronic pain patients to better understand pain as a sensory characteristic of dreaming. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 02.10.2025